Gene networks, brain networks: understanding schizophrenia - Weinberger, Daniel (Henry Stewart Talks, 2012)
Genomics and the future of psychiatry, Schizophrenia susceptibility genes, The GWAS approach, Behavior, brain functions & networks, Efficiency, dynamics & connectivity of different brain areas, Realistic phenotypic models, Polymorphisms and "psychiatric" genes, Epistatic interactions between various genes, Comparisons of genotype risk groups